Comprometimento políticos dos professores: resgate e busca nas tramas das práticas escolares - Balsan, Etiane Fagundes Braga (2012)
This work was aimed to investigate the level of politicization of teachers and whether this affects the political commitment of these workers outside the educational context of public schools in Santa Maria, with reference to current educational policies that have the autonomy, a key democracy feature of school management. In this sense, the knowledge of how and why the politicization of teachers, taking into consideration the historical, social, political and economic factors, underlie the thinking and work of these workers becomes a possibility for discussion, understanding and building an effective and conscious commitment to education in its social sense. In this form, not only the teachers, but also all that are involved in the educational work of the school must reflect and be aware of who they are, where they stand and to whom and for whom they work and struggle, which corresponds to making a critical inventory, conscious of themselves and their work in a contextualized way. To this end, the research was based on a qualitative approach, in one critical perspective, being the participant observation and focus group techniques used to collect data and the information obtained analyzed by content analysis. It became evident that teachers' work is extremely fragmented along the lines of factory work and reinforcement for technical education much present in the school concepts and practices. In this arrangement, the work force is more than common sense that the practice, pointing to the political apathy in relation to the profession and social reality, but the possible withdrawal, resistance and political commitment in relation to education and society. These categories occurred for the fact that the teachers themselves have the conscience needed before seeing themselves as this category of workers in order to constitute their professional identity. To meet this, the continuing education in the school from their needs is shown as the greatest ally in this process of political and technical training of teachers and, therefore, the reconstruction of school work. As a result, this work sought to contribute to studies that address the construction of citizenship, based on the politicization of teachers with reference to the political commitment of the working class, as has become one of the prerogatives for a more equitable education and a truly democratic society. Based on this position, therefore, an urgent and necessary discussion of the historical-critical work of the teacher and the school is advocated in the capitalist context with a view to understanding and combating the social function of this educational institutions and concomitant to the responsibility and role of the teachers in this work.